2021
DOI: 10.1101/2021.05.12.443802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluid intelligence and naturalistic task impairments after focal brain lesions

Abstract: Classical executive tasks, such as Wisconsin card-sorting and verbal fluency, are widely used as tests of frontal lobe control functions. Since the pioneering work of Shallice and Burgess (1991), it has been known that complex, naturalistic tasks can capture deficits that are missed in these classical tests. Matching this finding, deficits in several classical tasks are predicted by loss of fluid intelligence, linked to damage in a specific cortical 'multiple-demand' (MD) network, while deficits in a more natu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…These findings can also be contextualized with respect to past research looking at the functional neural correlates of fluid intelligence. Across a range of studies fluid intelligence has been associated with regions in the frontopartietal network (Barbey et al, 2014;Gläscher et al, 2010;Mitchell et al, 2023;Momi et al, 2020;Samu et al, 2017;Smith et al, 2022;Woolgar et al, 2010). We found that YA relied on the mPFC and IPL regions of this network, in line with past research.…”
Section: Nodal Efficiencysupporting
confidence: 89%
“…These findings can also be contextualized with respect to past research looking at the functional neural correlates of fluid intelligence. Across a range of studies fluid intelligence has been associated with regions in the frontopartietal network (Barbey et al, 2014;Gläscher et al, 2010;Mitchell et al, 2023;Momi et al, 2020;Samu et al, 2017;Smith et al, 2022;Woolgar et al, 2010). We found that YA relied on the mPFC and IPL regions of this network, in line with past research.…”
Section: Nodal Efficiencysupporting
confidence: 89%
“…Sensitivity analysis indicated robustness to moderate confounders, suggesting a direct effect, although with uncertain direction. We chose to treat IQ as the outcome variable, because this is what we would ultimately hope to improve, and because lesion and neuro-stimulation studies suggest that the integrity and function of frontoparietal networks do causally influence IQ (Glascher et al, 2010; Woolgar et al, 2010; Barbey et al, 2014; Momi et al, 2020; Smith et al, 2022). Although it is hard to imagine experimental manipulations of IQ that are not causally dependent on neural responses, we would not claim that the neural response to cognitive demand is unaffected by IQ.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in fluid intelligence correlate with MDN activity (Gray et al, 2003; Lee et al, 2006; Tschentscher et al, 2017; Assem et al, 2020b) and with its connectivity to other brain networks (Cole et al, 2012). The impact of focal lesions (Glascher et al, 2010; Woolgar et al, 2010; Barbey et al, 2014; Woolgar et al, 2018; Smith et al, 2022) and transient transcranial stimulation (Momi et al, 2020) suggests these regions’ causal role in supporting fluid intelligence. We therefore test the possibility that functional differences in MDN activation mediate fluid intelligence decline during healthy aging (Phillips and Della Sala, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of how the brain’s structure and function interact largely comes from observing differences in brain structure, such as across individuals (Mišić et al, 2016) or following brain injury (Smith et al, 2022), and then systematically linking these differences to brain function or behavioral outcomes. But how do these relationships between structure, function and behavior emerge in the first place ?…”
Section: Introductionmentioning
confidence: 99%